2022
DOI: 10.3389/fpls.2022.936572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and identification of advanced lentil interspecific derivatives resulted in the development of early maturing, high yielding, and disease-resistant cultivars under Indian agro-ecological conditions

Abstract: The genetic base revealed by pedigree records of the majority of released cultivars appears to be narrow in major pulse crops, including lentils, because of the frequent use of the same parents and their derivatives in crop improvement programs. Therefore, corrective measures are needed to widen the genetic base by involving the genetic resources of a distinct gene pool. In this direction, rigorous efforts were made to introgress wild Lens taxa, L. culinaris ssp. orientalis, and L. ervoides into the background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Besides biotic and abiotic stresses, the lentil is also challenged by a relatively narrow genetic base. The limited genetic diversity in modern lentil varieties has become a significant concern for improving lentil crop (Holme et al, 2019;Singh et al, 2022). As a result, the full production potential remains unrealized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides biotic and abiotic stresses, the lentil is also challenged by a relatively narrow genetic base. The limited genetic diversity in modern lentil varieties has become a significant concern for improving lentil crop (Holme et al, 2019;Singh et al, 2022). As a result, the full production potential remains unrealized.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, efforts were made to assess the genetic diversity in lentil and studies supported the incorporation of genetic resources from distinct gene pools (Langridge and Waugh, 2019). Further, it was also demonstrated that the wild relatives of lentil exhibit significant levels of genetic variation (Singh et al, 2022). Recently, a total of 2324 lentil accessions were evaluated for the identification of trait-specific germplasm (Tripathi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation